2018
DOI: 10.1111/1751-7915.13258
|View full text |Cite
|
Sign up to set email alerts
|

Random peptide mixtures as new crop protection agents

Abstract: SummaryMany types of crops are severely affected by at least one important bacterial disease. Chemical control of bacterial plant diseases in the field vastly relies on copper‐based bactericides, yet with limited efficacy. In this study, we explored the potential of two random peptide mixture (RPM) models as novel crop protection agents. These unique peptide mixtures consist of random combination of l‐phenylalanine and l‐ or d‐lysine (FK‐20 and FdK‐20, respectively) along the 20 mer chain length of the peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 36 publications
(35 reference statements)
0
30
0
Order By: Relevance
“…As in the case of bacteriophages, the greatest effectiveness is achieved when cocktails with well-known and properly selected compositions are used. Since small-molecule peptides are easy to reproduce, the technology of production is more convenient due to the easier process of synthesis of corresponding peptide variants [ 110 , 161 ]. Since it has been shown that some AMPs can only act against a narrow spectrum of species [ 162 ], the possibility of modification of their primary sequences allows the development of safe and stable AMPs that are specifically for the selected pathogens, with strictly targeted action against such bacteria as E. coli, Salmonella Pullorum, and Pseudomonas aeruginosa [ 160 , 163 ].…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…As in the case of bacteriophages, the greatest effectiveness is achieved when cocktails with well-known and properly selected compositions are used. Since small-molecule peptides are easy to reproduce, the technology of production is more convenient due to the easier process of synthesis of corresponding peptide variants [ 110 , 161 ]. Since it has been shown that some AMPs can only act against a narrow spectrum of species [ 162 ], the possibility of modification of their primary sequences allows the development of safe and stable AMPs that are specifically for the selected pathogens, with strictly targeted action against such bacteria as E. coli, Salmonella Pullorum, and Pseudomonas aeruginosa [ 160 , 163 ].…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…In the last few years, diverse AMPs have been reported to possess a high bactericidal activity against several phytopathogenic bacteria [ 48 , 49 , 50 , 51 , 52 ]. The plant pathogenic Pseudomonas genus has obtained some attention as a target for the development of new treatments based on AMPs [ 53 , 54 , 55 , 56 , 57 ]. Particularly, different AMPs were found to have a bactericidal effect on Psa by disrupting its membrane, at different ranges of concentration [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a possible mechanism of functioning of this peptide conjugated with high temperatures has been hypothesized, leading to condensation of the phospholipidic bilayer and consequent membrane destabilization that leads to cell death without pore formation [ 71 ]. AMPs have also been highlighted for their synergic potential when mixed together [ 54 , 72 , 73 ]. Despite most of these AMPs having revealed antimicrobial activity to clinical bacterial isolates, their action towards phytopathogenic bacteria is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The development of AMPs offers an effective method to prevent bacterial diseases. [15][16][17] Examples include AMPs overexpressed by transgenic crops, which have been demonstrated to exhibit broad-spectrum antimicrobial activities. [18][19][20] However, the expressing of AMPs in transgenic crops have low stability and are susceptible to protease degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The specificity of AMPs toward bacterial membranes is thought to reduce the propensity of bacterial resistance development. The development of AMPs offers an effective method to prevent bacterial diseases 15–17 . Examples include AMPs overexpressed by transgenic crops, which have been demonstrated to exhibit broad‐spectrum antimicrobial activities 18–20 .…”
Section: Introductionmentioning
confidence: 99%